Lipossomas: Estrategia biotecnologica para liberacao controlada e direcionamento intracelular de farmacos com efeito antimicobacteriano - Oliveira, Anselmo Gomes de [UNESP]; Scarpa, M. V. [UNESP]; Leite, Clarice Queico Fujimura [UNESP] (My University, 1997)
This text highlights the state of research related with the application of liposomes in the control of drug delivery and drug target to intracellular bacterial diseases, such as the tuberculosis. Liposome have several pharmaceutical applications and this article is primarily focused on the potential of this agregate on drug encapsalation especially antimycobacterial compounds. Case studies in which liposomes have successfully been used to improve pharmacological drug effect are presented. Mechanisms involved in intracellular drug delivery, possibilities of application, research and development efforts to address these objectives are discussed.
Liposomes: Biotechnological strategies for controlled delivery and intracellular target with antimycobacterial drugs.
Keywords: antibiotics; delivery control; intracellular target; liposomes; tuberculosis; aminoglycoside antibiotic agent; antibiotic agent; clindamycin; liposome; streptomycin; drug delivery system; drug targeting; encapsulation; endocytosis; human; infection; intravenous drug administration; mycobacteriosis; oral drug administration; phagocytosis; review